Lifestyle behavior interventions delivered using technology in childhood, adolescent, and young adult cancer survivors: A systematic review. Issue 1 (28th July 2016) - Kopp, Lisa M.; Gastelum, Zachary; Guerrero, Christian H.; Howe, Carol L.; Hingorani, Pooja; Hingle, Melanie
Abstract: Childhood, adolescent, and young adult cancer survivors demonstrate increased cardio‐metabolic risk factors, which are amenable to lifestyle changes. The use of technology to impact lifestyle change expands previously limited intervention access, yet little is known about its use. We summarized lifestyle interventions for survivors delivered using technology, finding six studies, primarily targeting physical activity. Study samples were small and durations ranged from 5 to 16 weeks and outcomes modest. Participants were older, white, survivors of leukemia or brain tumors, and the majority received Web‐based interventions. Study quality was moderate. Few technology‐based interventions have been developed, suggesting an area of opportunity for survivors.